Pengaruh Latihan Isometrik Untuk Menurunkan Tekanan Darah Pada Penderita Hipertensi - Naldi, Febria; Juwita, Lisavina; Silvia, Silvia (Universitas Fort De Kock Bukittinggi, 2022)
Background: Non-pharmacological therapy is one of the right choices forpeople with hypertension as an effort to control blood pressure. Pakan SalasaCommunity Health Center is one of the health centers with a fairly high findingof hypertension patients, which is an average of 30 hypertension patients permonth in 2020. This study aimed to determine The Effect of Isometric Exerciseto decrease the Blood Pressure of Hypertension Patients. Methods: The typeof this research was pre-experimental with a one group pretest posttest designapproach. It was carried out on April - June 2021 with 10 respondents werechosen as the samples. The data were collected through blood pressureobservation sheet. Then, it was analyzed by univariate and bivariate analysisby using paired t-test. Results: There was a difference in the average bloodpressure of respondents before and after the intervention with an averagedifference of 12.5/9 mmHg and p value = 0.005 where there was a significant decrease in blood pressure after the intervention. Conclusion: Inshort, it can be concluded that regular isometric exercise had a significanteffect on reducing blood pressure in patients with hypertension. It is expectedthat people with hypertension will doing physical activity with isometricexercises on a regular basis which is proven to be effective in lowering bloodpressure. Keywords:Isometric, Blood Pressure,Hypertension